Antimicrobial susceptibility pattern of multidrug resistant typhoidal Salmonella isolates at Bangabandhu Sheikh Mujib Medical University (Bangladesh Journal of Medical Microbiology, 2021)
Typhoid fever is a major public health problem in the developing world caused by Salmonella Typhi and Salmonella Paratyphi A. Multidrug resistant (MDR) Salmonella has emerged as a cause of concern. This study was done to evaluate status in antimicrobial susceptibility pattern of Salmonella Typhi and Salmonella Paratyphi A from blood culture isolates in Bangabandhu Sheikh Mujib Medical University during the period of September 2018 to August 2019. Suspected Salmonella spp. was collected from blood culture samples and identification was done by conventional microbiological procedure. Antimicrobial susceptibility test was performed by Kirby Bauer disc diffusion method and minimum inhibitory concentration (MIC) of ciprofloxacin was determined by agar dilution method following 2018 guideline of CLSI. Of total 160 isolates studied, 98 (61.3%) were S. Typhi and 62 (38.7%) were S. Paratyphi A. Sensitivity to ampicillin, chloramphenicol and cotrimoxazole was 83.1%, 87.5% and 89.3% respectively. Majority of the Salmonella isolates were in ciprofloxacin intermediate susceptible category by MIC determination (83.8%). Most of all (95.6%) isolates were resistant by pefloxacin disc diffusion test. All the isolates were 100% sensitive to ceftriaxone, cefixime and cefepime; and sensitivity to azithromycin was 31.9%. Isolates showed a high degree of susceptibility to ampicillin, cotrimoxazole and chloramphenicol. Thus, these antibiotics may once again be useful for the management of typhoid fever.Bangladesh J Med Microbiol 2021; 15 (2): 19-22